Study On The Impact Of Online Consumer Reviews On Online Consumer Purchasing Decision - Aiswarya.C.S, Dr. Indu Manish Kumar (International Journal of Advanced Science and Technology, 2020)
Online Consumer Review Platform Is An Emerging Market Phenomenon That Is Increasingly Influencing The Purchase Decision Of Consumers. Huge Volume Of Information And Shopping Experience Of Consumers About The Products Are Available Through Different Online Review Platforms. This Study Tries To Understand The Impact Of Online Consumer Review On Purchasing Decision. The Study Was Mainly Focused On Ernakulam District. This Study Found Out That The Online Consumer Review Platforms Create An Impact On The Consumers’ Purchasing Decision.